N(2)-Modified 2-aminopurine ribonucleosides as minor-groove-modulating adenosine replacements in duplex RNA - Peacock, Hayden (2010)
[Image: see text] Nucleoside analogs that project substituents into the minor groove when incorporated into duplex RNA perturb the binding of proteins and can affect base pairing specificity. The synthesis of 2-aminopurine ribonucleoside analogs and their phosphoramidites, their incorporation into duplex RNA, their post-synthetic modification via Cu-catalyzed azide-alkyne cycloaddition (CuAAC) and their effect on duplex stability and base pairing specificity is described.